Analysis of the Impact of Moian Beach Tourism Development on Local Community Income from the Perspective of Sustainable Tourism - Fadila Lutfiana; Herwin Mopangga; Irawati Abdul (Universitas Muhammadiyah Palu, 2026)
This research aims to: (1) Determine the impact of the development of Moian Beach tourism object on increasing local community income; (2) Formulate development strategies for Moian Beach tourism based on SWOT Analysis in order to establish it as a sustainable tourism destination; and (3) Identify obstacles and issues in the development of beach tourism and formulate appropriate solutions.. The type of research used is descriptive qualitative with a simple quantitative approach. Data collection techniques were carried out through observation, interviews, and distributing questionnaires to respondents consisting of managers/BUMDes, local communities, and tourists. Data analysis was conducted using descriptive analysis methods, IFAS-EFAS matrix analysis, as well as SWOT and TOWS analysis. The results show that: An income increase of 34.8% indicates that the management of Moian Beach tourism by BUMDes has provided a positive economic impact on the local community. Furthermore, there is a multiplier effect mechanism, where the circulation of money is not only enjoyed by managers but also impacts the income increase of traders, service providers, and the wider community. Based on the calculation results, the IFAS matrix obtained a score of 2.88 and the EFAS matrix obtained a score of 2.81. These results place Moian Beach in Quadrant I on the strategic map, meaning it is in a very advantageous position with strong internal strengths supported by great external opportunities. The most appropriate strategy to implement is an Aggressive Strategy (Growth Strategy), which is to maximize existing strengths to seize market opportunities, carry out development expansion, and expand promotion. However, several obstacles were found in the implementation, such as limited infrastructure, less professional human resource capacity, and profit-sharing management that has not been fully equitable. Therefore, the concept of sustainable tourism is very important to be applied to balance economic aspects, socio-cultural aspects, and environmental preservation. The conclusion of this study suggests improvements to management, enhancement of facilities, and the establishment of firm village regulations so that economic benefits can be felt fairly and sustainably by the present and future generations.